Single-atom catalysis enabled by high-energy metastable structures. Issue 10 (16th February 2023) - Xia, Zhaoming; Yin, Yue; Li, Jun; Xiao, Hai
Abstract : A high-energy metastable structure in an extremely small proportion that is difficult to identify can play a key role in delivering single-atom catalysis. This shakes the common assumption adopted in studies of single-atom catalysis. Abstract : Owing to limited degrees of freedom, the active sites of stable single-atom catalyst (SAC) often have one structure that is energetically much lower than other local-minimum structures. Thus, the SAC adopts one lowest-energy structure (LES) with an overwhelmingly larger proportion than any other high-energy metastable structure (HEMS), and the LES is commonly assumed to be solely responsible for the catalytic performance of an SAC. Herein, we demonstrate with SACs anchored on CeO2 that the HEMS of an SAC, even though its proportion remains several orders of magnitude lower than the LES throughout the catalytic reaction, can dictate catalysis with extraordinary activity arising from its unique coordination environment and oxidation state. Thus, we unravel the key role of HEMS-enabled catalysis in single-atom catalysis, which shakes the common assumption in the studies of SACs and urges new developments in both experiment and theory to identify and exploit catalysis via HEMSs.